Graphene oxide – Based supercapacitors from agricultural wastes: A step to mass production of highly efficient electrodes for electrical transportation systems. (May 2020) - Tamilselvi, R.; Ramesh, M.; Lekshmi, G.S.; Bazaka, Olha; Levchenko, Igor; Bazaka, Kateryna; Mandhakini, M.
Abstract: Supercapacitors and other innovative devices for electric energy generation and storage could significantly improve ecological situation in large densely populated cities. However, for this to become reality, supercapacitors should be produced en masse via a clean, green technology from the ecologically friendly material, preferably from abundant, sustainable resources, such as agricultural waste that is a by-product of other technological cycles. Many types of agricultural waste could be considered as an abundant, low-cost carbon source for large-scale fabrication of graphene-type materials. Here, we demonstrate that widely available coconut waste can be efficiently converted into reduced graphene oxide via simple catalytic oxidation using ferrocene as an efficient and low-cost catalyst. The structure and morphology of the as-prepared materials were characterized by XRD, SEM, and TEM techniques. The results confirmed the formation of high-quality reduced graphene oxide. The as-prepared graphene oxide was then analyzed as an electrode material for supercapacitor applications. We have found that the material exhibits high performance as an electric double layer capacitor (EDLC) and demonstrates excellent cyclic stability. Therefore, the reduced graphene oxide prepared via a simple, green process from this type of agricultural waste could be a good candidate of the supercapacitor electrodes. Graphical abstract: Image 1 Highlights: Reduced graphene oxide was successfully synthesized from coconut shell and coconut coir. Simple process at low temperature was successfully implemented. Reduced graphene oxide was tested as a super-capacitor electrodes showing very stable performance. This method presents an efficient pathway for synthesis of Reduced graphene oxide for flexible super-capacitor devices.